An evaluation of cloud-based mobile services with limited capacity: a linear approach - Skourletopoulos, Georgios; Mavromoustakis, Constandinos X.; Mastorakis, George; Batalla, Jordi Mongay; Sahalos, John N. (Soft computing (Berlin, Germany), 2017)
Mobile computing is pervading networks at an increasing speed as mobile devices are used with diverse forms of wireless technologies to access data. This paper evaluates different cloud-supported mobile services subject to limited capacity, as the selection of a service may introduce additional costs, such as those that derive from the additional amount of memory required for processing. In this context, a novel linear model and algorithm in the mobile cloud computing environment are proposed from the service capacity perspective, considering the cost that derives from the unused capacity. The probability of overutilization or underutilization of the selected service is also researched, once a linear growth in the number of users occurs. To further make effective and strategic investment decisions when selecting the appropriate cloud-based mobile service to lease off, the model formulation is based on a cost–benefit appraisal. The proposed quantification approach is evaluated with respect to four different case scenarios, exploiting a web tool that has been developed as a proof of concept and implementing the algorithm to calculate and compare the benefits and costs in the mobile cloud-based service level.